2003
DOI: 10.1046/j.1471-4159.2003.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin associated redox‐active iron is increased in the substantia nigra of patients with Parkinson's disease

Abstract: Degeneration of dopaminergic neurones during Parkinson's disease is most extensive in the subpopulation of melanizedneurones located in the substantia nigra pars compacta. Neuromelanin is a dark pigment produced in the dopaminergic neurones of the human substantia nigra and has the ability to bind a variety of metal ions, especially iron. Post-mortem analyses of the human brain have established that oxidative stress and iron content are enhanced in association with neuronal death. As redox-active iron (free Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(151 citation statements)
references
References 40 publications
8
139
0
4
Order By: Relevance
“…As a result, redox-active Fe could be released and involved in a Fenton-like reaction leading to an increased production of oxidative radicals. The results of Faucheux et al [24] showed that the redox activity of NM aggregates in a group of parkinsonian patients increased significantly (by 69%) and was highest in patients with the most severe neuronal loss. Such an overloading of NM with redox-active elements may contribute to oxidative stress and intraneuronal damage in patients with PD [24].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a result, redox-active Fe could be released and involved in a Fenton-like reaction leading to an increased production of oxidative radicals. The results of Faucheux et al [24] showed that the redox activity of NM aggregates in a group of parkinsonian patients increased significantly (by 69%) and was highest in patients with the most severe neuronal loss. Such an overloading of NM with redox-active elements may contribute to oxidative stress and intraneuronal damage in patients with PD [24].…”
Section: Introductionmentioning
confidence: 95%
“…The results of Faucheux et al [24] showed that the redox activity of NM aggregates in a group of parkinsonian patients increased significantly (by 69%) and was highest in patients with the most severe neuronal loss. Such an overloading of NM with redox-active elements may contribute to oxidative stress and intraneuronal damage in patients with PD [24]. On the other hand, it is necessary to mention that extraneuronal NM from dying neurons is phagocytosed by microglia and is associated with its activation.…”
Section: Introductionmentioning
confidence: 95%
“…Disruptions to transition metal concentration homeostasis (such as Mn, Fe, Cu and Zn) in the brain are implicated in neurodegenerative disorders such an Alzheimer's, Parkinson's and Multiple Sclerosis [25][26][27][28] where a common symptom of these diseases is demyelination -a loss of the protein/lipid complex myelin. The myelin sheath is an insulating protein and fatty layer that encapsulates the axons of neurons in the central and peripheral nervous system of vertebrates to improve conduction of electrical signals.…”
Section: -2mentioning
confidence: 99%
“…Post-mortem analyses of the substantia nigra in PD patients have shown effects of oxidative stress with a decrease in glutathione (GSH) levels, increased levels of iron, neuromelanin associated redox-active iron, lipid peroxidation, protein oxidation and DNA damage (Jenner and Olanow 1998, Faucheux et al 2003, Dexter et al 1989). These changes may directly induce nigral cell degeneration via oxidative stress or render neurons susceptible to the actions of toxins.…”
Section: Parkinson's Disease Pathologymentioning
confidence: 99%
“…The effects of oxidative stress are demonstrated in PD patients who have decreased GSH levels, increased levels of iron, neuromelanin associated redox-active iron, lipid peroxidation, protein oxidation and DNA damage in the substantia nigra (Jenner and Olanow 1998, Faucheux et al 2003, Dexter et al 1989. Antioxidant therapy has been suggested to ameliorate these effects.…”
Section: Antioxidant Therapymentioning
confidence: 99%